Nanoindentation-Based Micro-Mechanical and Electrochemical Properties of Quench-Hardened, Tempered Low-Carbon Steel - Muhammad ArslanHafeez; Muhammad Usman; Muhammad Adnan Arshad; Malik AdeelUmer (Crystals, 2020)
The nanoindentation technique is widely used to measure the micro-scale mechanical properties of various materials. Herein, the nanoindentation-based micro-mechanical and electrochemical properties of low-carbon steel were investigated after quench hardening and tempering processes. The steel was produced on a laboratory scale and subjected to quench hardening separately in two different media-water and brine (10 wt% NaCl)-and subsequent moderate temperature tempering. Microstructure analysis revealed that the lath martensite phase formed after all heat treatments, having different carbon percentages ranging from 0.26% to 0.58%. A ferrite phase was also observed in the microstructure in three different morphologies, i.e., allotriomorphic ferrite, idiomorphic ferrite, and Widmanstätten ferrite. Nanoindentation analysis showed that the brine quench hardening process provided a maximum twofold improvement in indentation hardness and a 51% improvement in stiffness with a 30% reduction in reduced elastic modulus compared with as-received steel. Electrochemical performance was also evaluated in a 1% HNO3 solution. The water quench-hardened and tempered sample exhibited the highest corrosion resistance, whereas the brine quench-hardened sample exhibited the lowest corrosion resistance among all heat-treated samples.